Mental representation and the discovery of new strategies - Csaszar, Felipe A.; Levinthal, Daniel A. (Strategic Management Journal, 2016)
Research summary : Managers' mental representations affect the perceived payoffs and alternatives that managers consider. Thus, mental representations affect how managers search for profitable strategies as well as the quality of strategies they discover. To study how mental representation and search interact, we formally model the dual search over possible representations and over policy choices of a strategy “landscape.” We analyze when it is preferable to emphasize searching for the best policies rather than the best mental representation, and vice versa. We show that, in the long run, a balance between the two search modes not only results in better expected performance, but also reduces the variation in performance. Additionally, the article describes conditions under which increased accuracy of mental representations can actually worsen firm performance . Managerial summary : Managers' mental representations affect the perceived payoffs and alternatives that managers consider. Thus, mental representations affect the quality of strategies managers can discover. We analyze a computer simulation of how managers use mental representations to search for strategies. This sheds light on how managers should deal with the trade‐off between searching for policies and searching for representations; that is, whether managers should think creatively about how to represent a strategy problem or whether they should just stick to the current problem understanding, and try to find ways to improve performance as suggested by the current representation. We provide insight regarding the balance between the two search modes and describe conditions under which increasingly accurate mental representations can worsen firm performance . Copyright © 2015 John Wiley & Sons, Ltd.